2020
DOI: 10.1038/s41598-020-79074-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of hotspots of tetrapod biodiversity and the challenges of open-access data scarcity

Abstract: The uneven spatial distribution of biodiversity is a defining feature of nature. In fact, the implementation of conservation actions both locally and globally has progressively been guided by the identification of biodiversity ‘hotspots’ (areas with exceptional biodiversity). However, different regions of the world differ drastically in the availability of fine-scale data on the diversity and distribution of species, thus limiting the potential to assess their local environmental priorities. Within South Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 92 publications
0
11
0
3
Order By: Relevance
“…Our results revealed that there are areas, both inside and outside the global protected area network, where botanical sampling efforts have been inadequate or non-existent. This incomplete data can result in spatial disparities between biodiversity and protected area networks (68). Our findings demonstrated that locations with a potentially high number of rare and diverse woody angiosperms are present in the data-deficient areas, suggesting a conservation gap of the current protected areas.…”
Section: Discussionmentioning
confidence: 79%
“…Our results revealed that there are areas, both inside and outside the global protected area network, where botanical sampling efforts have been inadequate or non-existent. This incomplete data can result in spatial disparities between biodiversity and protected area networks (68). Our findings demonstrated that locations with a potentially high number of rare and diverse woody angiosperms are present in the data-deficient areas, suggesting a conservation gap of the current protected areas.…”
Section: Discussionmentioning
confidence: 79%
“…In the global context, amphibians constitute the most threatened vertebrate group, according to IUCN red lists categorization (Button & Borzée 2021). Notably the region of this experimental platform is located at a rich region in amphibian species (Grattarola et al 2020;Laufer et al 2021). Amphibians, with their heightened sensitivity to environmental shifts and relatively limited mobility in comparison to other vertebrates, emerge as invaluable indicators within experiments of this nature (Böll et al 2013).…”
Section: Amphibian Monitoringmentioning
confidence: 99%
“…The choice of the data resolution is a classic issue in conservation science that has been discussed in two separate contexts, i.e., mathematical suboptimality and cost-efficiency issues resulting from spatial biases [33,34], and spatial aggregation of conservation areas to improve long-term conservation efficacy [35]. Biodiversity data are spatially, temporally, and taxonomically biased [36][37][38][39] due to shortages of survey efforts [40] and a lack of mobilization of potentially usable information, including undigitized records [37,41]. Such incomplete and biased information can degrade the performance of conservation planning [42].…”
Section: Toward Robust Scp In the Era Of Biodiversity Big Datamentioning
confidence: 99%